Sodré sem Cais: António Franco Alexandre e a cidade sobre-exposta - SERRA, Pedro (Ángulo Recto. Revista de estudios sobre la ciudad como espacio plural, 2009)
Essay on the relations of the poetry of Portuguese poet António Franco Alexandre and the city of Lisbon. Lisbon, imperial metropolis, in the remnants of a suspended memory of its historical aura, is refracted as a ’ville surexposée’ or an ’over-exposed city’, Paul Virilio’s notion that elaborates on the metastasis of suburban cities, place where the urban object is no longer self-evident.